Bourdieu and the Sociology of Music Consumption: A Critical Assessment of Recent Developments. Issue 3 (19th February 2013) - Prior, Nick
Abstract The French sociologist Pierre Bourdieu has been an extraordinarily influential figure in the sociology of music. For over three decades, his concepts have helped to generate both empirical and theoretical interventions in the field of study. His impact on the sociology of music taste, in particular, has been profound, his ideas directly informing our understandings of how musical preferences reflect and reproduce inequalities between social classes. But, recently his legacy has been under question and newer approaches to the music/society problematic have emerged. These have made important claims about the nature of the sociological enterprise when confronted with the specificity of cultural works, as well as how social change impacts on our relations with musical forms. This paper takes stock of the impact of Bourdieu's ideas on the sociology of music, the debates sparked in their wake and the attempt at something like a "post‐Bourdieusian" sociology more faithful to music's material properties. It will ask to what extent Bourdieu's claims about social stratification and music consumption are still relevant and whether they are sophisticated enough to deal with the specific ways that we interact with musical forms.